2007
DOI: 10.1155/2007/80572
|View full text |Cite
|
Sign up to set email alerts
|

High-Risk Cutaneous Squamous Cell Carcinoma of the Head and Neck

Abstract: Nonmelanoma skin cancers (squamous cell and basal cell carcinomas) occur at an epidemic rate in many countries with the worldwide incidence increasing. The sun-exposed head and neck are the most frequent sites for these cancers to arise and in most patients diagnosed with a cutaneous squamous cell carcinoma, local treatment is usually curative. However, a subset is diagnosed with a high-risk cutaneous squamous cell carcinoma. High-risk factors include size (>2 cm), thickness/depth of invasion (>4 mm), recurre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
65
2
3

Year Published

2010
2010
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 86 publications
(75 citation statements)
references
References 43 publications
(50 reference statements)
5
65
2
3
Order By: Relevance
“…6,21 A large study conducted by Brantsch et al with 615 patients designated tumor depth and histological differentiation as risk factors for metastatic disease, with 75% of lesions being <2 cm, confirming the opinion held by Veness et al, that even small lesions have a significant metastatic potential. 8,22 Lymphatic metastases were identified in 23.3% of the patients, which is slightly higher than previously reported rate, ranging from 0.3% to 20.7%. The incidence reflects the practice environment of the authors, since the patients referred to our comprehensive cancer center are more likely to suffer from aggressive or advanced disease.…”
Section: Discussioncontrasting
confidence: 61%
See 3 more Smart Citations
“…6,21 A large study conducted by Brantsch et al with 615 patients designated tumor depth and histological differentiation as risk factors for metastatic disease, with 75% of lesions being <2 cm, confirming the opinion held by Veness et al, that even small lesions have a significant metastatic potential. 8,22 Lymphatic metastases were identified in 23.3% of the patients, which is slightly higher than previously reported rate, ranging from 0.3% to 20.7%. The incidence reflects the practice environment of the authors, since the patients referred to our comprehensive cancer center are more likely to suffer from aggressive or advanced disease.…”
Section: Discussioncontrasting
confidence: 61%
“…The median 10-year survival rate for patients with regional metastatic disease was 12.1±9.8%, and for the entire patient cohort 45.5±10.2%, which is consistent with published results. 8 Analysis of the entire population with head and neck CSCC, including patients with regional disease (n=103) showed that women are affected significantly later (p<0.0012), probably due to a lesser degree of sun exposure and longer life expectancy. 19,20 Detailed histopathological analysis has identified perineural invasion as a risk factor for nodal metastasis.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Veness et al 69 have reported 266 cases of metastatic cSCC, with 162 (61%) involving the parotid gland. On this basis, authors have suggested parotidectomy in cases of T3 or T4 lesions with high-risk features.…”
Section: Prophylactic Parotidectomymentioning
confidence: 99%